Effect of thinning and slashing on forage phytomass from a Caatinga of Petrolina, Pernambuco, Brazil - de Albuquerque, Severino G.; Bandeira, George Ricardo L. (Pesquisa Agropecuaria Brasileira, 1995)
The effect of woodland manipulation on forage phytomass was studied in a Caatinga of Petrolina, PE, Brazil. There were five treatments: 1)Control of native vegetation; 2)Thinning 1/3 of shrub canopy cover; 3)Thinning 2/3 of shrub cover; 4)Caatinga slashing; and 5)Treatment 4 + burning. Slashing and burning were carried out in September/84, and thinning done in January/85. Herbaceous mass in the control was 528 kg/ha, half grasses and half forbs, in the only evaluation made (May/85). The slashed area had a higher grass mass than the control (675 vs 251 kg/ha). Forb mass increased from treatment 1 to 5, but only these two were significantly different (1,609 vs 277 kg/ha). Neoglaziovia variegata showed the opposite trend, decreasing from treatment 1 to 5 (1,413 vs 25 kg/ha). Slashing was superior to the other treatments in shrub mass, including slashing and burning (706 vs 317 kg/ha), and caused an increase in the tree stratum forage mass over the other treatments (236 vs 50-78 kg/ha), due to coppicing.